Migration and Labour Choice in Albania - Azzarri, Carlo (2012)
Very little analysis exists of the income-generating strategies of Albanian households, and how this relates to income dynamics, people's mobility and poverty. Results show that agricultural, migration and human capital assets have a differential impact across livelihood choices, and that this impact varies by gender and age. Two areas of policy concern derive from this analysis. First, migration is clearly crucial for the economic future of Albania, in terms of fuelling economic development in rural areas, and in reducing excess labour supply and poverty. The suggestion of a potential disincentive effect on labour effort and participation is, however, worrying, as it would have implications in terms of missed opportunities for development. Second, agriculture appears to be more of a survival strategy than part of a poverty exit strategy.